High-entropy sulfide negative electrode material, lithium ion battery and preparation and application of high-entropy sulfide negative electrode material and lithium ion battery
By introducing Cu elements and doping Li into high-entropy sulfides, the electron conductivity and ion dispersion are improved, and configuration entropy is improved through multi-element doping, the poor circulation performance of existing high-entropy sulfide electrode materials is solved. The problem is that high specific capacity and high rate charging and discharging performance have been improved.
Patent Information
- Application Number
- CN202411489021.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-07
AI Technical Summary
The existing high entropy sulfide electrode materials have relatively poor long cycle properties in lithium-ion batteries, and cannot fully meet the circulation requirements of lithium-ion batteries.
FeNiCoCuLiSx high-entropy sulfide material is used to improve electron conductivity by introducing Cu elements, doping Li elements to improve ion dispersion, and multi-element doping to increase configuration entropy, thereby inhibiting the volume expansion of the electrode material during charge and discharge.
The long cycle stability, high specific capacity and high rate charge and discharge performance of high entropy sulfide materials are significantly improved, and the cycle performance and energy density of lithium-ion batteries are enhanced.
Smart Images

Figure CN119400856A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to high entropy sulfide materials, in particular to high entropy sulfide which can be used as negative electrode of lithium ion battery. Background Art
[0002] The theoretical capacity of traditional graphite negative electrode materials is limited (372mAh / g), which cannot fully meet the energy density requirements of current lithium-ion batteries. Although traditional metal sulfides have a high theoretical specific capacity, the volume and structure of the negative electrode of the transition metal will change during the charge and discharge process, reducing the cycle performance of the battery. The application of high entropy sulfides with high configurational entropy in lithium-ion batteries can partially overcome the above problems.
[0003] However, the high entropy sulfide electrode materials in the prior art have relatively poor long-term cyclability and cannot fully meet the cycling requirements of lithium-ion batteries. Summary of the invention
[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a new high entropy sulfide negative electrode material and lithium ion battery and its preparation and application. The high entropy sulfide has excellent long cycle stability, high specific capacity and high rate charge and discharge performance.
[0005] The technical solution of the present invention is as follows:
[0006] A high entropy sulfide, which is a compound FeNiCoCuLiS x , where x = 5.5-6.5.
[0007] The high entropy sulfide of the present invention introduces the Cu element to improve the electronic conductivity of the electrode material; the Li element is doped to improve the ion dispersion in the material. At the same time, it is doped with multiple elements to improve the configuration entropy of the material, inhibit the volume expansion of the electrode material during charging and discharging, and improve the long-cycle stability of the electrode material and the high-rate charging and discharging performance.
[0008] The present invention further provides a method for preparing the high entropy sulfide, which comprises:
[0009] (1) Put Fe(NO 3 ) 3 ,Ni(NO 3 ) 2 、Co(NO 3 ) 2 、Cu(NO 3 ) 2 、LiNO 3 Mixing and dissolving the first organic solvent and the template agent in a molar ratio of 1:1:1:1:1 to obtain a mixed solution;
[0010] (2) reacting the mixed solution at 150-170° C. to obtain a first suspension, adding a first dispersant to the first suspension, and then centrifuging to obtain a precursor and drying to obtain a dried precursor;
[0011] (3) adding thioacetamide and a second organic solvent to the dried precursor until the solid is completely dispersed to obtain a second suspension;
[0012] (4) reacting the second suspension at 140-160° C. to obtain a third suspension, dispersing and centrifuging the third suspension using a first dispersant and a second dispersant, respectively, and drying the obtained product to obtain the high entropy sulfide;
[0013] Wherein, the template is glycerol, the first dispersant is an organic dispersant, and the second dispersant is water.
[0014] According to some preferred embodiments, the first organic solvent is isopropanol.
[0015] According to some preferred embodiments, the second organic solvent is ethanol.
[0016] According to some preferred embodiments, the first dispersant is ethanol.
[0017] According to some preferred embodiments, the volume ratio of the isopropanol to the glycerol is 5-6:1.
[0018] According to some preferred embodiments, the mass ratio of the dried precursor to the thioacetamide is 1:1.5-2.
[0019] According to some preferred embodiments, the reaction time of step (2) is 8 to 12 hours.
[0020] According to some preferred embodiments, the reaction time of step (4) is 6 to 10 hours.
[0021] According to some preferred embodiments, the method for preparing the high entropy sulfide specifically comprises:
[0022] (1) Put Fe(NO 3 ) 3 ,Ni(NO 3 ) 2 、Co(NO 3 ) 2 、Cu(NO 3 ) 2 、LiNO 3 Mix in a molar ratio of 1:1:1:1:1, add isopropanol and glycerol in a volume ratio of 34:6, and stir until all the solids are dissolved to obtain a mixed solution;
[0023] (2) reacting the mixed solution in a hydrothermal reactor at 160° C. for 10 h to obtain a first suspension, adding dispersant ethanol to the first suspension, and centrifuging to obtain a precursor, and vacuum drying the obtained precursor at 80° C. for 8 h to obtain a dried precursor;
[0024] (3) weighing the dried precursor and thioacetamide in a mass ratio of 1:1.67, adding ethanol and stirring until the solid is completely dispersed to obtain a second suspension;
[0025] (4) reacting the second suspension in a high-pressure reactor at 150° C. for 8 h to obtain a third suspension, dispersing the third suspension with ethanol and centrifuging it with water, respectively, and drying the obtained product to obtain the high-entropy sulfide.
[0026] The present invention further provides application of the high entropy sulfide on the negative electrode of a lithium ion battery.
[0027] According to some preferred embodiments, the application includes: mixing and stirring the high entropy sulfide, a binder and a conductive agent in a solvent N-methylpyrrolidone, and then grinding to obtain a negative electrode slurry, wherein the binder is selected from polyvinylidene fluoride, and the conductive agent is selected from Ketjen black.
[0028] According to some preferred embodiments, the mass ratio of the high entropy sulfide, the binder and the conductive agent is 7:1.5:1.5.
[0029] The present invention further provides a lithium ion battery obtained according to the high entropy sulfide.
[0030] The beneficial effects of the present invention include:
[0031] (1) The high entropy sulfide of the present invention has a high ion transfer rate, which helps to accelerate the insertion and deinsertion and transfer process of lithium ions, greatly improves the charge and discharge efficiency of the battery, and improves its cycle performance at high current density;
[0032] (2) The high entropy sulfide of the present invention has a micron-sphere structure, which is beneficial for buffering the volume expansion of the active material, reducing structural damage during the cycle process, and improving the cycle stability of the battery;
[0033] (3) The high entropy sulfide of the present invention can provide more active sites through the lattice defects brought by the high entropy effect, thereby increasing the lithium storage performance;
[0034] (4) The high entropy sulfide of the present invention is doped with Li ions, which effectively promotes the dispersion of elements. The discharge capacity of the negative electrode material is ≥750 mAh g -1 , and has high rate performance;
[0035] (5) The preparation method of the present invention is simple and efficient, and can obtain high entropy sulfide with many advantages in lithium ion battery negative electrode application;
[0036] (6) The preparation method of the present invention uses a glycerol template, generates a glycerol precursor through a first solvothermal reaction, and reacts the glycerol precursor with thioacetamide to generate a high entropy sulfide through a second solvothermal reaction; the above two-step solvothermal method can make the metal ions more dispersed and more evenly distributed in the material, and obtain uniform nanoparticles. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 XRD comparison diagram of the high entropy sulfide material prepared in Example 1 and the sulfide material prepared in Comparative Examples 1-2;
[0038] Figure 2 The high entropy sulfide material FeNiCoCuLiS prepared in Example 1 x EDS diagram of
[0039] Figure 3 The high entropy sulfide material FeNiCoCuLiS prepared in Example 1 x SEM images of
[0040] Figure 4 A comparison chart of the ratios of the high entropy sulfide material prepared in Example 1 and the sulfide material prepared in Comparative Examples 1-3 as negative electrode materials for lithium batteries;
[0041] Figure 5 This is a cycle comparison chart of the high entropy sulfide material prepared in Example 1 and the sulfide materials prepared in Comparative Examples 1-3 as negative electrode materials for lithium batteries. DETAILED DESCRIPTION
[0042] The present invention is described in detail below in conjunction with the embodiments and drawings, but it should be understood that the embodiments and drawings are only used to exemplify the present invention and do not constitute any limitation on the protection scope of the present invention. All reasonable changes and combinations within the scope of the inventive concept of the present invention fall within the protection scope of the present invention.
[0043] Example 1
[0044] The high entropy sulfide of the present invention is prepared by the following steps:
[0045] (1) Put Fe(NO 3 ) 3 ,Ni(NO 3 ) 2 、Co(NO 3 ) 2 、Cu(NO 3 ) 2、LiNO 3 Add into a beaker in a molar ratio of 1:1:1:1:1 (0.5 mmol each), and add 34 ml of isopropanol and 6 ml of glycerol, and stir until all the solids are dissolved to obtain a mixed solution;
[0046] (2) transferring the obtained mixed solution to a high-pressure hydrothermal reactor, reacting it in a forced air oven at 160° C. for 10 hours, adding dispersant ethanol to the obtained suspension, and centrifuging it three times to obtain a precursor;
[0047] (3) The precursor was vacuum dried in a vacuum oven at 80° C. for 8 hours, 100 mg of the dried precursor and 167 mg of thioacetamide were weighed, and 50 ml of ethanol were added and stirred for 3 hours until the solid was completely dispersed to obtain a suspension;
[0048] (4) The suspension obtained in step (3) was transferred to a high-pressure reactor, reacted in a forced air oven at 150° C. for 8 hours, and the suspension after the reaction was centrifuged several times with dispersant ethanol and deionized water, respectively, and dried in a vacuum oven to obtain a high-entropy sulfide FeNiCoCuLiS x .
[0049] The obtained high entropy sulfide FeNiCoCuLiS x The XRD results are shown in the attached Figure 1 As shown, it can be seen that the characteristic peak of the unit sulfide in the high entropy sulfide weakens and disappears, indicating that the high entropy material is successfully prepared and that the doping of Li element reduces the particle size of the material.
[0050] The obtained high entropy sulfide FeNiCoCuLiS x The EDS is attached Figure 2 As shown, it shows that the transition metal elements Fe, Ni, Co, Cu and S are almost uniformly distributed in the high entropy phase (Li can hardly be displayed under EDS), and the concentrations of the above metal atoms in the atomic layer are detected to be 10at.%, 9at.%, 9at.%, and 11at.%, respectively. According to the configuration entropy calculation formula shown in the following formula (1), it can be seen that the configuration entropy S of the compound is greater than 1.5R, and it is a high entropy material.
[0051]
[0052] Among them, S is the configuration entropy of the material, R is the molar gas constant R = 8.314 J·mol-1·K -1 , N is the number of metal elements in the material, x i is the mole fraction of the element in the sl1 lattice, x j is the mole fraction of the element in the sl2 lattice.
[0053] The obtained high entropy sulfide FeNiCoCuLiSx The SEM images are shown in the attached Figure 3 As shown, it can be seen that the high entropy sulfide has a micron-spherical structure, which is beneficial to buffer the volume expansion of the active material, reduce structural damage during the cycle process, and improve the cycle stability of the battery.
[0054] Comparative Example 1
[0055] Comparative sulfides were prepared by the following steps:
[0056] (1) Put Fe(NO 3 ) 3 ,Ni(NO 3 ) 2 、Co(NO 3 ) 2 、Cu(NO 3 ) 2 Add into a beaker in a molar ratio of 1:1:1:1 (0.625 mmol each), and add 34 ml of isopropanol and 6 ml of glycerol, and stir until all the solids are dissolved to obtain a mixed solution;
[0057] (2) transferring the obtained mixed solution to a high-pressure hydrothermal reactor, reacting it in a forced air oven at 160° C. for 10 hours, adding dispersant ethanol to the obtained suspension, and centrifuging it three times to obtain a precursor;
[0058] (3) The precursor was vacuum dried in a vacuum oven at 80° C. for 8 hours, 100 mg of the dried precursor and 167 mg of thioacetamide were weighed, and 50 ml of ethanol were added and stirred for 3 hours until the solid was completely dispersed to obtain a suspension;
[0059] (4) The suspension obtained in step (3) was transferred to a high-pressure reactor and reacted in a forced air oven at 150° C. for 8 hours. The suspension after the reaction was centrifuged several times with dispersant ethanol and deionized water, respectively, and dried in a vacuum oven to obtain sulfide FeNiCoCuS x .
[0060] Comparative Example 2
[0061] Comparative sulfides were prepared by the following steps:
[0062] (1) Put Fe(NO 3 ) 3 ,Ni(NO 3 ) 2 、Co(NO 3 ) 2 Add them into a beaker in a molar ratio of 1:1:1 (0.833 mmol each), and add 34 ml of isopropanol and 6 ml of glycerol, and stir until all the solids are dissolved to obtain a mixed solution;
[0063] (2) transferring the obtained mixed solution to a high-pressure hydrothermal reactor, reacting it in a forced air oven at 160° C. for 10 hours, adding dispersant ethanol to the obtained suspension, and centrifuging it three times to obtain a precursor;
[0064] (3) The precursor was vacuum dried in a vacuum oven at 80° C. for 8 hours, 100 mg of the dried precursor and 167 mg of thioacetamide were weighed, and 50 ml of ethanol were added and stirred for 3 hours until the solid was completely dispersed to obtain a suspension;
[0065] (4) The suspension obtained in step (3) was transferred to a high-pressure reactor and reacted in a forced air oven at 150° C. for 8 hours. The suspension after the reaction was centrifuged several times with dispersant ethanol and deionized water, respectively, and dried in a vacuum oven to obtain sulfide FeNiCoS x .
[0066] Comparative Example 3
[0067] Comparative sulfides were prepared by the following steps:
[0068] (1) 2.5 mmol of Fe(NO 3 ) 3 Add to a beaker, add 34 ml of isopropanol and 6 ml of glycerol, and stir until all the solids are dissolved to obtain a mixed solution;
[0069] (2) transferring the obtained mixed solution to a high-pressure hydrothermal reactor, reacting it in a forced air oven at 160° C. for 10 hours, adding dispersant ethanol to the obtained suspension, and centrifuging it three times to obtain a precursor;
[0070] (3) The precursor was vacuum dried in a vacuum oven at 80° C. for 8 hours, 100 mg of the dried precursor and 167 mg of thioacetamide were weighed, and 50 ml of ethanol were added and stirred for 3 hours until the solid was completely dispersed to obtain a suspension;
[0071] (4) The suspension obtained in step (3) was transferred to a high-pressure reactor and reacted in a forced air oven at 150° C. for 8 hours. The suspension after the reaction was centrifuged several times with dispersant ethanol and deionized water, respectively, and dried in a vacuum oven to obtain sulfide FeS 2 .
[0072] The high entropy sulfide or comparative sulfide obtained in Example 1 and Comparative Examples 1-3 is prepared as a negative electrode material for a lithium battery. The preparation method is as follows: using N-methylpyrrolidone as a solvent, the sulfide, the conductive agent (ketjen black) and the binder (polyvinylidene fluoride) are mixed uniformly at a mass ratio of 7:1.5:1.5, and the solvent is added and stirred after grinding to obtain a negative electrode slurry for a lithium battery. The negative electrode slurry for a lithium battery is uniformly scraped on a Cu foil with a thickness of 50 μm, and the Cu foil is heated at 120° C. for 12 h in a vacuum drying oven to remove the solvent, and then cut into discs with a diameter of 12 mm to obtain a pole piece, and the pole piece, diaphragm, lithium sheet, spring sheet, gasket, positive electrode shell and negative electrode shell are assembled into a lithium battery in a glove box filled with argon gas, and the electrochemical performance thereof is tested, including:
[0073] The specific capacity of the first cycle and the specific capacity after the 500th cycle were tested at a current density of 1000 mA / g. The results are shown in Table 1 below:
[0074] Table 1
[0075]
[0076]
[0077] It can be seen that after 100 cycles, the specific capacity of Comparative Example 3 has a significant decrease, decaying to 401 mAh / g, while the specific capacity decay of Comparative Example 2, Comparative Example 1 and Example 1 is not obvious. After 500 cycles, the specific capacities of Comparative Example 1, Comparative Example 2 and Comparative Example 3 are significantly reduced, decaying to 295 mAh / g, 318 mAh / g and 146 mAh / g, respectively, while the capacity of Example 1 remains at 727 mAh / g, with a good capacity retention rate.
[0078] Carry out the magnification test, the results are as follows Figure 4 As shown, it can be seen that at a current density of 100 mA / g, the reversible capacities of Comparative Example 3, Comparative Example 2, Comparative Example 1 and Example 1 at the 10th cycle are 855, 892, 882, 866 and 980 mAh / g, respectively. After 30 cycles, the discharge powers of Comparative Example 3, Comparative Example 2, Comparative Example 1 and Example 1 at a current density of 2.0 A / g are 511, 748, 852 and 843 mAh / g, respectively, and the discharge powers at a current density of 5.0 A / g are 472, 680, 796 and 761 mAh / g, respectively, which are much higher than Comparative Example 3. It shows that Example 1 and Comparative Example 1 exhibit better high rate performance at different current densities.
[0079] The cycle performance test was carried out and the results are shown in the attached Figure 5As shown, it can be seen that at the 100th cycle, the specific capacities of Comparative Example 2, Comparative Example 1 and Example 1 were 580, 748 and 735 mAh / g, respectively, and the capacity did not decrease significantly. As the number of cycles increased, the reversible capacity of Comparative Example 3 decreased significantly, providing only 402 mAh / g specific capacity at the 100th cycle. Although the specific capacity of Example 1 was slightly lower than that of Comparative Example 1 before the 100th cycle, the specific capacity of Example 1 was higher than that of Comparative Example 1 after the 100th cycle. In particular, when the current density of Example 1 was 1000 mA / g at about 240 cycles, the specific capacity was as high as 865 mAh / g, much higher than other comparative samples. At the 500th cycle, the reversible specific capacities of Comparative Example 3, Comparative Example 2, Comparative Example 1 and Example 1 were 146, 318, 295 and 724 mAh / g, respectively, indicating that the cycle performance of Example 1 is more stable than other samples.
[0080] The above embodiments are only preferred implementations of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A high entropy sulfide, characterized in that: It is a compound FeNiCoCuLiS x , where x = 5.5-6.
5.
2. The method for preparing high entropy sulfide according to claim 1, characterized in that: It includes: (1) mixing and dissolving Fe(NO3)3, Ni(NO3)2, Co(NO3)2, Cu(NO3)2, and LiNO3 in a first organic solvent and a template agent at a molar ratio of 1:1:1:1:1 to obtain a mixed solution; (2) reacting the mixed solution at 150-170° C. to obtain a first suspension, adding a first dispersant to the first suspension, and then centrifuging and drying to obtain a precursor; (3) adding thioacetamide and a second organic solvent to the dried precursor until the solid is completely dispersed to obtain a second suspension; (4) reacting the second suspension at 140-160° C. to obtain a third suspension, dispersing and centrifuging the third suspension using a first dispersant and a second dispersant, respectively, and drying the obtained product to obtain the high entropy sulfide; Wherein, the template is glycerol, the first dispersant is an organic dispersant, and the second dispersant is water.
3. The method for preparing high entropy sulfide according to claim 2, characterized in that: in, The first organic solvent is isopropanol; and / or, the second organic solvent is ethanol; and / or, the first dispersant is ethanol.
4. The method for preparing high entropy sulfide according to claim 3, characterized in that: in, The volume ratio of the isopropanol to the glycerol is 5-6:1, and / or the mass ratio of the dried precursor to the thioacetamide is 1:1.5-2.
5. The method for preparing high entropy sulfide according to claim 2, characterized in that: in, The reaction time of step (2) is 8 to 12 hours; and / or the reaction time of step (4) is 6 to 10 hours.
6. The method for preparing high entropy sulfide according to claim 2, characterized in that: It includes: (1) Fe(NO3)3, Ni(NO3)2, Co(NO3)2, Cu(NO3)2, and LiNO3 are mixed in a molar ratio of 1:1:1:1:1, and isopropanol and glycerol are added in a volume ratio of 34:6, and stirred until all the solids are dissolved to obtain a mixed solution; (2) reacting the mixed solution in a hydrothermal reactor at 160° C. for 10 h to obtain a first suspension, adding dispersant ethanol to the first suspension, and centrifuging to obtain a precursor, and vacuum drying the obtained precursor at 80° C. for 8 h to obtain a dried precursor; (3) weighing the dried precursor and thioacetamide in a mass ratio of 1:1.67, adding ethanol and stirring until the solid is completely dispersed to obtain a second suspension; (4) reacting the second suspension in a high-pressure reactor at 150° C. for 8 h to obtain a third suspension, dispersing the third suspension with ethanol and centrifuging it with water, respectively, and drying the obtained product to obtain the high-entropy sulfide.
7. Use of the high entropy sulfide according to claim 1 or the high entropy sulfide prepared by the preparation method according to any one of claims 1 to 6 in the negative electrode of a lithium ion battery.
8. The use according to claim 7, characterized in that: It includes: The high entropy sulfide, the binder and the conductive agent are mixed and stirred in a solvent of N-methylpyrrolidone, and then ground to obtain a negative electrode slurry, wherein the binder is selected from polyvinylidene fluoride, and the conductive agent is selected from Ketjen black.
9. The use according to claim 8, characterized in that: The mass ratio of the high entropy sulfide, the binder and the conductive agent is 7:1.5:1.
5.
10. A lithium ion battery using the high entropy sulfide according to claim 1 or the high entropy sulfide prepared by the preparation method according to any one of claims 1 to 6.